PEDESTRIAN PATH LIVABILITY CONCEPT IN THE RTH AREA RELIGIOUS MONUMENT OF KENDARI CITY - Nahdatunnisa Nahdatunnisa; Wahyudi S.I Wahyudi S.I; Henny Adi; M.Arzal Tahir (Proceedings of the 1st International Conference on Social Science (ICSS), 2022)
Green Open Space is a city-forming element that has an important role in maintaining environmentalbalance and environmental sustainability in urban areas. Parks in addition to having an ecologicalfunction, can be used as a place for socializing and economic activities. Thus, the park as a city facilitymust have a good level of livability for the convenience of its visitors. Pedestrian trails located in thegreen open space area of Kendari City are parks with indications of decreased livability. This studyaims to analyze the feasibility and performance of pedestrian pathways in the green open space area ofKendari City against applicable standards such as: accessibility, connectivity, circulation, security,safety, noise, beauty, climate and cleanliness and determine the priority of services needed to improveperformance. pedestrian facilities. The purpose of this study was to evaluate the service andperformance of pedestrian paths in the Green Open Space (RTH) of Kendari City by using 27 researchvariables which were a combination of quantitative and qualitative research, with a sample of 399people. respondents. This study uses the Importance Performance Analysis (IPA) method in assessingthe performance of the existing pedestrian path, and the Customer Satisfaction Index (CSI) todetermine the user satisfaction index for the services received. The results obtained in this study arerelated to evaluating the performance of the existing pedestrian path which consists of goodcategories: facilities for pedestrians with special needs (guiding blocks), availability of road markings,availability of crossing lanes, security systems (cctv, security posts), speed control facilities ,cleanliness level. adequate/ordinary categories: dimensions of pedestrian paths, lighting of pedestrianpaths, differences in the level of height of pedestrian paths with road bodies, availability of pedestrianpath markings and signs/signals, surface texture of materials, seating, climate (shady), shelter/shelter ,Vegetation/shade plants, Number and quality of trash bins. bad/bad categories: the availability oframps, pedestrian paths connected to urban transportation elements, continuity of pedestrian paths,obstructions in pedestrian paths, crossings, and noise suppression facilities, while the pedestrian pathuser satisfaction index for services is only in the category quite satisfied with a value of 65.57%.